Current applications of endoscopic suturing - Stavropoulos, Stavros N (World J Gastrointest Endosc, 2015)
Endoscopic suturing had previously been considered an experimental procedure only performed in a few centers and often by surgeons. Now, however, endoscopic suturing has evolved sufficiently to be easily implemented during procedures and is more commonly used by gastroenterologists. We have employed the Apollo OverStitch suturing device in a variety of ways including closure of perforations, closure of full thickness defects in the gastrointestinal wall created during endoscopic full thickness resection, closure of mucosotomies during peroral endoscopic myotomy, stent fixation, fistula closure, post endoscopic submucosal dissection, endoscopic mucosal resection and Natural Orifice Transluminal Endoscopic Surgery defect closures, post-bariatric surgery gastrojejunal anastomosis revision and primary sleeve gastroplasty.